Adding Appropriate Fiber in Diet Increases Diversity and Metabolic Capacity of Distal Gut Microbiota Without Altering Fiber Digestibility and Growth Rate of Finishing Pig - Pu, Guang; Li, Pinghua; Du, Taoran; Niu, Qing; Fan, Lijuan; Wang, Huan; Liu, Hang; Li, Kaijun; Niu, Peipei; Wu, Chengwu; Zhou, Wuduo; Huang, Ruihua (Frontiers in Microbiology, 2020)
The digestion ability of pigs to dietary fiber is derived from the microbiota of their distal intestine. However, the tolerance of pigs to high dietary fiber and the changes of microbiota profile with fiber levels in pigs are still unclear. To investigate the changes of gut microbiota with dietary fiber and its relationship with fiber digestibility, we conducted comparative analyses of growth rate, apparent fiber digestibility, gut microbiota and short-chain fatty acid (SCFA) profiles in Chinese Suhuai pigs feeding diets with different defatted rice bran (DFRB) fiber levels. We found that dietary fiber level had no effect on the growth rate of Suhuai pigs. Although the apparent digestibility of Cellulose, insoluble dietary fiber (IDF) and total dietary fiber (TDF) decreased with dietary fiber level, we found that the apparent digestibility of Cellulose, IDF and TDF of Suhuai pigs was not changed when provided with diet containing 19.10% TDF. The pigs provided with diet containing 19.10% TDF had higher microbial richness, proportions of several fiber-degrading bacteria taxa at genus level and predicted microbial functions (e.g., carbohydrate metabolism, energy metabolism) in cecum compared to those fed with basal diet. In addition, the fiber-induced increasing of fiber-degrading bacteria promoted the SCFAs metabolism, which potentially helped Suhuai pigs to maintain growth rate. However, too much fiber (24.11%) could not increase the related microbiota, so the fiber digestibility decreased. Together, our data suggest that appropriate fiber level could increase the diversity and metabolic capacity of distal gut microbiota to improve the utilization efficiency of fiber resources without altering the growth rate of pigs.